Institutional partnerships in multi-hazard early warning systems : a compilation of seven national good practices and guiding principles - Golnaraghi, Maryam (Springer Berlin Heidelberg, 2012)
This book documents seven examples of Early Warning Systems for hydrometeorological and other hazards that have proven effective in reducing losses due to these hazards. The cases studied encompass a variety of climatic regimes and stages of economic development, raging across the industrialized countries of Germany, France, Japan and the United States, to Bangladesh, the island nation of Cuba and the mega-city of Shanghai. Demonstrated characteristics of these exemplary cases are synthesized into ten guiding principles for successful early warning systems that will, it is hoped, prove useful to countries seeking to develop or strengthen such systems within their own borders.